2003
DOI: 10.1002/glia.10138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PINCH in Schwann cells and DRG neurons: Shuttling and signaling after nerve injury

Abstract: Particularly interesting new cysteine-histidine rich protein (PINCH) is a double zinc finger domain (LIM)-only adapter protein that functions to recruit the integrin-linked kinase (ILK) to sites of integrin activation. Genetic studies have shown that PINCH and ILK are required for integrin signaling. Since integrin activation is associated with Schwann cell migration, neurite outgrowth and regeneration, this study examined PINCH in the normal peripheral nervous system and after chronic constriction injury (CCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…Consistent with such binding properties, the first LIM domain of PINCH has been shown to bind ILK and the fourth LIM domain the SH2/SH3 adaptor protein Nck2 (or Grb4), which in turn can associate with several receptor tyrosine kinases and thereby links integrins to growth factor signalling (Tu et al, 1998). Furthermore, mammalian PINCH1 and 2 and C. elegans PINCH have been shown to be present in the nucleus of a variety of cell types (Hobert et al, 1999;Zhang et al, 2002a;Campana et al, 2003). Whether nuclear PINCH1 and 2 binds nuclear proteins and/or DNA, however, is not known.…”
Section: Introductionmentioning
confidence: 86%
“…Consistent with such binding properties, the first LIM domain of PINCH has been shown to bind ILK and the fourth LIM domain the SH2/SH3 adaptor protein Nck2 (or Grb4), which in turn can associate with several receptor tyrosine kinases and thereby links integrins to growth factor signalling (Tu et al, 1998). Furthermore, mammalian PINCH1 and 2 and C. elegans PINCH have been shown to be present in the nucleus of a variety of cell types (Hobert et al, 1999;Zhang et al, 2002a;Campana et al, 2003). Whether nuclear PINCH1 and 2 binds nuclear proteins and/or DNA, however, is not known.…”
Section: Introductionmentioning
confidence: 86%
“…The preparation, specificity and reliability of the rabbit polyclonal PINCH antibody used in the study were described previously [7,14]. Five-um sections from paraffin-embedded tissue blocks were deparaffinized, hydrated and rinsed in distilled H 2 O.…”
Section: Immunohistological Staining and Evaluationmentioning
confidence: 99%
“…Since the migfilin mutant lacking an NES has increased transcription-and differentiation-promoting activities (Akazawa et al, 2004), migfilin(s) probably also has higher transcription-and differentiationpromoting activity. It has been shown that several other LIM-containing focal adhesion proteins, including zyxin (Nix and Beckerle, 1997), LPP (for 'lipoma preferred partner') (Petit et al, 2000), Ajuba (Kanungo et al, 2000), Trip6 (for 'thyroid hormone interacting protein 6') (Wang and Gilmore, 2001), Hic-5 (for 'hydrogen peroxide-inducible clone 5') (Shibanuma et al, 2003;Shibanuma et al, 1997;Yang et al, 2000), PINCH-1 (Campana et al, 2003) and PINCH-2 (Zhang et al, 2002), can also be transported to the nucleus. Although much remains to be learned about their functions in the nucleus, currently available data suggest that they probably recognize different sets of nuclear targets and therefore mediate diverse nuclear activities.…”
Section: Cellular Functions Of Migfilinmentioning
confidence: 99%